Economies of Density, Scale and Scope in the Water Supply and Sewerage Sector: A Study of Four Developing and Transition Economies - Nauges, Celine (2012)
Using panel data, we estimate measures of density, scale and scope economies in four countries that differ substantially in their levels of economic development and in their piped water and sewerage coverage: Brazil, Moldova, Romania and Vietnam. We find evidence of economies of scale in Moldova, Romania and Vietnam. In Brazil, we cannot reject the null hypothesis of constant returns to scale. The results of this study show that the cost structure of water and sewerage utilities varies significantly within and between countries and over time.